X-Ray Observations of VY Scl-Type Nova-Like Binaries in the High and Low State - P. Zemko; M. Orio (Acta Polytechnica CTU Proceedings)
Four VY Scl-type nova-like systems were observed in X-rays both during the low and the high optical states. They are BZ Cam, MV Lyr, TT Ari, and V794 Aql. Using archival ROSAT, Swift and SUZAKU observations we found that the X-ray flux for BZ Cam is higher during the low state, but there is no supersoft X-ray source (SSS) that would indicate the thermonuclear burning predicted in a previous article. The X-ray flux is lower by a factor 2–10 in the low than the high state in other systems, and does not reflect the drop in ˙M inferred from optical and UV data. The best fit model for the X-ray spectra is a collisionally ionized plasma model. The X-ray flux may originate in a shocked wind or in accretion onto polar caps in intermediate polar systems that continues even during the low state.